Binding of meso-tetra (4-N-methylpyridyl) porphine to DNA. - Fiel, R J (1980)
The porphyrin photosensitizer, meso-Tetra (4-N-methyl-pyridyl) porphine tetraperchlorate is shown to unwind supercoiled ColEI DNA at a somewhat lower concentration than ethidium bromide. In contrast to this, the Fe(III) chelate of T4MPyP cannot unwind supercoiled DNA. It is concluded that these results corroborate our previous findings that, despite its large bulk, T4MPyP is fully capable of intercalating in DNA.